2013
DOI: 10.3892/etm.2013.959
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressive microRNA-424 inhibits osteosarcoma cell migration and invasion via targeting fatty acid synthase

Abstract: Numerous studies have recently suggested that miRNAs contribute to the development of various types of human cancer as well as to their invasive and metastatic capacities. The aim of this study was to investigate the functional significance of miR-424 and to identify its possible target genes in osteosarcoma (OS) cells. Previously, inhibition of fatty acid synthase (FASN) has been shown to suppress OS cell proliferation, invasion and migration. The prediction was made using the microRNA.org and TargetScan.huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 36 publications
4
48
0
2
Order By: Relevance
“…Few reports have mentioned the effects of miR-424 expression in lung cancer metastasis. However, miR-424 played crucial roles in osteosarcoma cells migration and invasion through targeting fatty acid synthase [30]. Besides, miR-424 is an contributor for prostate cancer metastasis via involving in biological including migration and invasion [31].…”
Section: Discussionmentioning
confidence: 99%
“…Few reports have mentioned the effects of miR-424 expression in lung cancer metastasis. However, miR-424 played crucial roles in osteosarcoma cells migration and invasion through targeting fatty acid synthase [30]. Besides, miR-424 is an contributor for prostate cancer metastasis via involving in biological including migration and invasion [31].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies (Llobet-Navas et al 2014a,b) and the new data shown here have revealed that this miRNA cluster modulates the expression of at least three well-known oncogenes (CDC25A, BCL-2, and IGF1R) in human and mouse primary breast cancers. Others have also shown that, in other cell types, this cluster targets additional genes involved in cell cycle progression (Nakashima et al 2010;Xu et al 2013b), angiogenesis (Ghosh et al 2010;Nakashima et al 2010), immune response (Xu et al 2016), cell metabolism (Long et al 2013), and cell adhesion (Chong et al 2014). Thus, we propose that aberrant high levels of these targets due to loss of miR-424(322)/ 503 support multiple hallmarks of cancer leading to tumorigenesis (Fig.…”
Section: Discussionmentioning
confidence: 57%
“…Study in Wu X et al revealed that the proliferation of human osteosarcoma was suppressed by downregulating Eag1 . Data from Long XH et al indicated that miR-424 suppresses osteosarcoma cell migration and invasion via targeting fatty acid synthase (Long et al, 2013). Another study claimed that the proliferation and invasion of osteosarcoma cells can be inhibited by miR376c by targeting the expression of transforming growth factor-alpha (Jin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%